2012
DOI: 10.1177/1753193411419952
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic deprivation and the epidemiology of carpal tunnel syndrome

Abstract: Deprivation has been recognized as a major determinant of health and is associated with several musculoskeletal conditions. This study examines the effect of deprivation on the incidence of carpal tunnel syndrome using a regional prospective audit database. Over a 6 year period there were 1564 patients diagnosed with CTS with an annual incidence of 72/100,000 population. There was a significant difference in population incidence of CTS from the most deprived (81/100,000) to the least deprived (62/100,000) (p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…The interaction between different knowledge and patients' multidisciplinary approach in pain clinics positions them as active subjects in the therapeutic process and provides a holistic vision to professionals, which makes clinical information more detailed and the diagnosis faster 9 . In our study, the sample has shown predominance of females, which reinforces the hypothesis of previous studies which have evidenced higher neuropathic pain prevalence among females 6,[10][11][12] . Hormonal differences, easiness to verbalize pain and lower tolerance to pain may explain such results 6 .…”
Section: Discussionsupporting
confidence: 91%
“…The interaction between different knowledge and patients' multidisciplinary approach in pain clinics positions them as active subjects in the therapeutic process and provides a holistic vision to professionals, which makes clinical information more detailed and the diagnosis faster 9 . In our study, the sample has shown predominance of females, which reinforces the hypothesis of previous studies which have evidenced higher neuropathic pain prevalence among females 6,[10][11][12] . Hormonal differences, easiness to verbalize pain and lower tolerance to pain may explain such results 6 .…”
Section: Discussionsupporting
confidence: 91%
“…Our diabetic patients did not present with a higher incidence of trigger digit, carpal tunnel syndrome or Dupuytren's disease. In their evaluation of 108 patients, Rottgers et al [36][37][38][39] arrived at the same conclusion, with 53% of his patients suVering from diabetes mellitus, that diabetes mellitus does not predispose to the concomitant presentation of trigger digit and carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of carpal tunnel syndrome varies from 51 to 125:100,000 being more frequent among females between 40 and 60 years of age 50,51 . However, a study aiming at evaluating clinical NP characteristics in carpal tunnel syndrome patients using painDETECT as questionnaire to distinguish NP has not shown significant differences among patients with and without NP; however pain intensity and night pain were higher for those with NP 52 .…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%